National Drug Resilience within the Legal Framework: An Analysis of Regulation and Implementation of Law Number 17 of 2023 - Tjandrawinata, Raymond R.; Heliany, Ina (International Journal of Science and Society, 2024)
National drug resilience is a fundamental pillar for achieving health independence and sovereignty in Indonesia. Strengthening this resilience has become a strategic mandate outlined in Law No. 17 of 2023 on Health, emphasizing the critical role of producing pharmaceuticals, vaccines, medical devices, and natural-based medicines to support the national healthcare system. This article examines the regulatory aspects, implementation, and challenges of realizing national drug resilience through a normative juridical approach. The integration of progressive legal theory, utilitarianism, and the welfare state model is the primary analytical framework for evaluating policy effectiveness. This approach is reinforced by a human rights perspective, particularly the right to health as enshrined in Article 28H of the 1945 Constitution and international frameworks such as ICESCR. The findings highlight that synergy among adaptive legal policies, strengthening biodiversity-based research and innovation, and supporting local industries are key to reducing dependence on imported materials and enhancing global competitiveness. This article contributes to local legal literature by integrating legal theory with human rights frameworks in the context of pharmaceutical policy while offering practical recommendations for supporting sustainable drug resilience policies. It provides a theoretical and strategic foundation for bolstering the national healthcare system through an inclusive and progressive legal approach.